2002
DOI: 10.1542/peds.109.4.e55
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Biochemical Markers of Growth in Children With Snoring and Obstructive Sleep Apnea

Abstract: ABSTRACT. Objective. The pathophysiological mechanisms of growth impairment frequently associated with the obstructive sleep apnea syndrome (OSAS) in children are poorly defined. The main objective of this study was to evaluate whether nighttime upper airway obstruction attributable to adenotonsillar hypertrophy and subsequent surgical treatment affect the circulating concentrations of insulin-like growth factor-I (IGF-I) and IGFbinding protein 3 (IGFBP-3) along with other growth parameters in children.Patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
142
2
19

Year Published

2005
2005
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 226 publications
(175 citation statements)
references
References 41 publications
12
142
2
19
Order By: Relevance
“…It is possible that sleep-related problems are discussed during the medical visit; however they are not Clinical manifestations found in this study are in agreement with literature data. The complaints that motivated the polysomnographic studies were mainly restless sleep, snoring, breathing breaks during sleep and labored breathing 4,21,23 . It was seen that breathing difficulty during sleep was an important symptom indicative of OSHAS, being more significant in children younger than 5 years of age.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that sleep-related problems are discussed during the medical visit; however they are not Clinical manifestations found in this study are in agreement with literature data. The complaints that motivated the polysomnographic studies were mainly restless sleep, snoring, breathing breaks during sleep and labored breathing 4,21,23 . It was seen that breathing difficulty during sleep was an important symptom indicative of OSHAS, being more significant in children younger than 5 years of age.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5] Adenotonsillar hypertrophy is the primary cause of OSAS in children, and is usually treated with adenotonsillectomy (AT). AT has been reported to accelerate weight [6][7][8][9][10][11][12][13][14] in children with baseline failure to thrive (FTT), 1,3,4,15 normal weight patients, 9,11,14,[16][17][18][19][20] obese individuals, 9,13,16,21,22 and infants. 10 The majority of studies also have demonstrated an increase in the height growth rate after AT for OSAS, 3,6,11,17,23,24 but other studies reported no significant differences.…”
Section: (Continued On Last Page)mentioning
confidence: 99%
“…[1][2][3] Significant complications of untreated OSA include learning difficulties. [4][5][6][7] behavioral problems, 8,9 failure to thrive, 10,11 pulmonary hypertension [12][13][14][15] and systemic hypertension. 16,17 Early diagnosis can decrease morbidity, 16 however the diagnosis of OSA is often delayed by months to years because of inadequate screening.…”
Section: Introductionmentioning
confidence: 99%